Penerapan Pengenal Bahasa Sunda Melalui Program Rebo Nyunda di TK Negeri Pembina Ciawigebang - Hilmalia Aina, Mila; Badroeni, Badroeni (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This study aims to describe: (1) the implementation of the Rebo Nyunda program in enhancing children's ability to use the Sundanese language at TK Negeri Pembina Ciawigebang, (2) the inhibiting factors and solutions in the implementation of the Rebo Nyunda program, and (3) the strategies used by teachers in organizing the program and their effectiveness. This research employs a qualitative method with a case study approach. The research subjects include the principal, teachers, and parents of the students, while the object of the research is the Rebo Nyunda program. Data collection techniques consist of structured interviews, observation, and document analysis. The data were analyzed descriptively through data reduction, data presentation, and drawing conclusions. The results show that the Rebo Nyunda program is carried out through the introduction of basic Sundanese vocabulary in daily activities and songs, allowing children to recognize and use basic Sundanese words. The obstacles include the lack of Sundanese language teachers and the daily use of Indonesian at home, which are addressed by encouraging the use of Sundanese every Wednesday at school. Teacher strategies involve introducing various traditional games to maintain children's interest, and the success of the program is observed through the children's active participation in Sundanese language activities